Farmer’s Pesticide Safety Management: A Study of Behaviour in Pesticide Storage and Rinse Houses Usage - Eka Rosanti; Ratih Andhika Akbar Rahma; Mahmudah Hamawi (Knowledge Dynamics, 2025)
Background: It is required to provide adequate equipment to optimize farmers' pesticide safety management. Pesticide storage and rinsing facilities are necessary to improve farmers' pesticide safety management practices. Water, personal protective equipment (PPE), a pesticide box, and a first-aid box are all included. This study focuses on describing farmer behaviour in terms of pesticide storage and the use of rinse homes. Methods: Seven farmers from X Village's farmer group participated in this qualitative study. In-depth semi-structured interviews and observation were used to gather data. Interviews were taped and transcribed word by word, then categorized and coded. The data was interpreted, and the outcomes were examined accordingly. Results: The findings revealed that the farmers did not make effective use of the amenities. They simply used the water facilities for hand washing and tank rinsing, and they only wore masks instead of full PPE. The findings revealed that farmers are aware of the dangers of pesticides, but they are comfortable with their old practices and rely on the farmer's habits. The pesticide box increases storing behaviour significantly. Farmers have also made use of the first-aid kit. Conclusion: According to this research, the provision of facilities has not been able to modify farmers' behaviour in pesticide safety management. The first step towards changing one's behaviour is to become aware of the problem. The more intensive contact between planners, farmers, and other stakeholders are essential.